Game Save The Sea! as an Education Media to Prevent Water Pollution - Alnando Harsono; Ridwan Sanjaya; Bernadinus Harnadi (Soegijapranata Catholic University, 2021)
Human’s ignorance is the most threatening factor to natural water sources on the system. The habit of littering and poor waste management often occurs in developing countries, especially Indonesia. Through an educational game this message could be delivered easier. This paper is intended to find ways for people to be more concerned with water pollution. The questionnaire and interview methods are used to search for pre-test and post-test data. From the pre-test data, “Save The Sea” mobile game is created which can help educate the public about the dangers of water pollution. After 5 times playing of once each day, game testing was conducted to 39 people and fill the questionnaire. Post test data result shows that the game succeeded in creating conditions where people were more concerned about water pollution.